Pravna narava zavezujoče informacije med teorijo in prakso - Kovač, Polonca (Podjetje in delo, 2016)
Advance ruling is an act, which has been regulated in Slovenia since 2006, following foreign models and customs rulings as administrative decisions in EU law. Advance ruling is issued, as stipulated by the Slovene Tax Procedure Act, in individual case, based on future or potential relevant facts. Therefore, a legal nature of this act is a hybrid one, since it is abstract and individual. The Slovene tax authority is furthermore rather restrictive at informing taxpayers; hence the use of this instrument is very low. The purpose of this article is to determine prevailing elements of this act and its legal character to enable legal protection and thus enhance its use. Advance ruling has legal effects, and especially judicial review should be guaranteed to taxpayers, regardless if they understand advance ruling as an administrative regulating or an administrative decision or a guarantee act. Legal certainty and stability of investors in Slovene and European market is pursued in this analysis as a guiding principle.
Keywords: davčni postopek; davki; Evropska unija; informacije; odločbe; upravni postopek